Reduction in operating voltage of AlGaN homojunction tunnel junction deep-UV light-emitting diodes by controlling impurity concentrations. (8th July 2021) - Nagata, Kengo; Makino, Hiroaki; Miwa, Hiroshi; Matsui, Shinichi; Boyama, Shinya; Saito, Yoshiki; Kushimoto, Maki; Honda, Yoshio; Takeuchi, Tetsuya; Amano, Hiroshi
Abstract: We reduced the operating voltage of AlGaN homojunction tunnel junction (TJ) deep-ultraviolet (UV) light-emitting diodes (LEDs) by two approaches: the suppression of carbon incorporation and the doping of a high concentration of silicon in an n + -AlGaN layer. The AlGaN homojunction TJ deep-UV LEDs had a significantly reduced forward voltage upon suppressing the incorporation of carbon in the n + -AlGaN layer. The suppression of electron compensation by carbon in nitrogen sites and the doping of a high concentration of silicon in an n + -AlGaN layer are important for reducing the operating voltage of AlGaN homojunction TJ deep-UV LEDs.